Antimicrobial Peptide K0-W6-Hya1 Induces Stable Structurally Modified Lipid Domains in Anionic Membranes - Enoki, Thais A.; Moreira-Silva, Isabela; Lorenzon, Esteban N.; Cilli, Eduardo M. [UNESP]; Perez, Katia R.; Riske, Karin A.; Lamy, M. Teresa (American Chemical Society (ACS), 2018)
Considering the known different mode of action of antimicrobial peptides in zwitterionic and anionic cell membranes, the present work compares the action of the antimicrobial peptide K0-W6-Hya1 (KIFGAIWPLALGALKNLIK-NH2) with zwitterionic and negatively charged model membranes, namely, liposomes composed of phosphatidylcholine (PC) and phosphatidylglycerol (PG) membranes, and a mixture of the two. Differential scanning calorimetry (DSC), steady state fluorescence of the Trp residue, dynamic light scattering (DLS), and measurement of the leakage of an entrapped fluorescent dye (carboxyfluorescein, CF) were performed with large unilamellar vesicles (LUVs). All techniques evidenced the different action of the peptide in zwitterionic and anionic vesicles. Trp fluorescence spectroscopy shows that the differences are related not only to the partition of the cationic peptide in zwitterionic and anionic membranes, but also to the different penetration depth of the peptide into the lipid bilayers: Trp goes deeper into negatively charged membranes, both in the gel and fluid phases, than into zwitterionic ones. DSC shows that the peptide is strongly attached to anionic bilayers, giving rise to the coexistence of two different lipid regions, one depleted of peptide and another one peptide-disturbed, possibly a stable or transient polar pore, considering the leakage of CF. This contrasts with the homogeneous effect produced by the peptide in zwitterionic membranes, probably related to peptide-membrane diffusion. Moreover, in mixed bilayers (PC:PG), the peptide sequesters negatively charged lipids, creating peptide-rich anionic lipid regions, strongly disturbing the membrane. The distinct structural interaction displayed by the peptide in PC and PG membranes could be related to the different mechanisms of action of the peptide in anionic prokaryotic and zwitterionic eukaryotic cell membranes.